Penentuan Umur Simpan Bumbu Rujak dalam Kemasan Botol Plastik Menggunakan Metode Arrhenius - Ida Ayu Agung Putri Trisiana Dewi; Ida Bagus Putu Gunadnya; Ida Ayu Rina Pratiwi Pudja (Jurnal BETA (Biosistem dan Teknik Pertanian), 2015)
The objectives of this research were: to determine critical parameters and to estimate it’s shelflife using Accelerated Shelf-Life Testing (ASLT) with Arrhenius method. Rujak seasoning that packed in plastic bottle was stored at three storage temperature 35oC, 45oC, and 55oC. Each room storage was loaded with three samples. This research was carried out for 25 days and observation was done every 5 days. The parameters observed included pH and sensory parameters, namely flavor, color, and salak aroma of the seasoning. Results showed that the critical parameter of rujak seasoning was pH and all quality parameters of rujak seasoning such as pH, flavor, color, and aroma followed first reaction order. By using extrapolation, the shelf-life of rujak seasoning packed in plastic bottle which stored at room temperature 28oC was 167 days (5,6 months)